An Investigation of the Effects of Alcohol Consumption and Alcohol Policies on Youth Risky Sexual Behaviors - Markowitz, Sara; Kaestner, Robert; Grossman, Michael (American Economic Review, 2005)
An Investigation of the Effects of Alcohol Consumption and Alcohol Policies on Youth Risky Sexual Behaviors by Sara Markowitz, Robert Kaestner and Michael Grossman. Published in volume 95, issue 2, pages 263-266 of American Economic Review, May 2005